Carbo‐Quinoids: Stability and Reversible Redox‐Proaromatic Character towards Carbo‐Benzenes1. (21st January 2015) - Cocq, Kévin; Maraval, Valérie; Saffon‐Merceron, Nathalie; Saquet, Alix; Poidevin, Corentin; Lepetit, Christine; Chauvin, Remi
Abstract The carbo‐mer of the para‐quinodimethane core is stable within in a bis(9‐fluorenylidene) derivative. Oxidation of this carbo‐quinoid with MnO2 in the presence of SnCl2 and ethanol affords the corresponding p‐bis(9‐ethoxy‐fluoren‐9‐yl)‐carbo‐benzene. The latter can be in turn converted back into the carbo‐quinoid by reduction with SnCl2, thus evidencing a chemical reversibility of the interconversion between a pro‐aromatic carbo‐quinoid and an aromatic carbo‐benzene, and is reminiscent of the behavior of the benzoquinone/hydroquinone redox couple (in the red–ox opposite sense).